(untitled) (Journal of Social Sciences Review, 2023)
The researchers focus on the TPACK framework, which is used to assess teachers’ understanding of how to use technology in the classroom. The goal of the model is to define the skills and knowledge teachers need to effectively integrate technology into their lessons. Teacher educators’ can better prepare their students for the problems of the modern world by applying the TPACK. Teachers need to have a high level of the ability to integrate their knowledge of subject matter, pedagogy, with the integration of technology. In the Pakistani setting, there is still a lack of technological integration in educational settings. The purpose of this research was to determine how well teacher educators in Karachi, Pakistan, use TPACK and associated domains in their classrooms for the preparation of future teachers. Teacher educators from private teacher education institutions of Karachi were conveniently sampled for this quantitative survey research study. Data was analyzed using SPSS, and the study’s measurement and structural models were put through their paces using Smart PLS. It is one of the more sophisticated programs for structural equation modeling that uses partial least squares (PLS-SEM). The study found that teachers educators’ technology and technological pedagogical knowledge significantly effects on their TPACK in a positive way. Conclusions and suggestions for further research are provided for implementing the TPACK framework in teacher education programs and designing learning strategies for enhancing instructors’ pedagogical skills in light of the study’s findings.